IMPACT OF PATENT DUCTUS ARTERIOSUS CLOSURE ON LINEAR GROWTH AND WEIGHT GAIN IN CHILDREN: A PROSPECTIVE COHORT STUDY - Widjaja, Sri Lilijanti; Putri, Pritania Prameswara; Artiko, Bagus; Anniazi, Masayu Lubna; Ahmadwirawan, Mylco Trisaputra (Masters Program in Public Health, Sebelas Maret University, 2026)
Background: Patent ductus arteriosus (PDA) can cause pulmonary circulatory volume overload and hemodynamic disturbances that result in feeding difficulties, recurrent infections, and growth retardation. PDA closure intervention is expected to improve physiological conditions, thereby supporting improvements in linear growth and weight gain. Subject and Methods: This prospective cohort study was conducted at Dr. Moewardi General Hospital from January 2024 to July 2025. The target population was children diagnosed with patent ductus arteriosus (PDA). Subject was all of pediatric PDA patients at Dr. Moewardi General Hospital Surakarta who underwent PDA closure procedures (total sampling). Subjects with complete anthropometric data such as body weight and height at PDA pre-procedure, with 3 and 6 months after PDA procedure (post-procedure) were selected. The dependent variables were changes in height (cm) and body weight (kg), measured using standard anthropometric methods. Data were analyzed using the Friedman test for repeated measures, followed by paired Wilcoxon tests with Bonferroni correction for post-hoc comparisons. Results: Total there were 48 children who underwent PDA closure with complete anthropometric data at PDA pre- and 3 to 6 months post-procedure. Mean height significantly increased 4.5% from 83,60 ± 26,23 cm at PDA pre-procedure to 87,34 ± 24,87 cm at 3 months post-procedure, and increased 8.1% to90,39 ± 23,64 cm at 6 months post-procedure( p<0,001). Mean body weight also significantly increased 9.3% from 11,49 ± 12,21 kg at PDA pre-procedure to 12,56 ± 11,93 kg at 3 months post-pocedure then increase 16.1% to 13,34 ± 11,88 kg at 6 months post-procedure (p<0,001). The height and weight of children with PDA closure increased over the observation period. Conclusion: PDA closure is associated with a significant increase in linear growth and weight gain up to 6 months post-procedure.